2001
DOI: 10.1054/bjoc.2001.2192
|View full text |Cite
|
Sign up to set email alerts
|

RCAS1 as a tumour progression marker: an independent negative prognostic factor in gallbladder cancer

Abstract: Receptor-binding cancer antigen expressed on SiSo cells (RCAS1) induces apoptosis in immune cells bearing the RCAS1 receptor. We sought to determine RCAS1 involvement in the origin and progression of gallbladder cancer, and also implications of RCAS1 for patient survival. RCAS1 expression was examined immunohistochemically in 110 surgically resected gallbladder specimens. The gallbladders represented 20 cases of cholecystitis with no associated pancreaticobiliary maljunction; 23 cases of cholecystitis with pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 14 publications
3
40
0
1
Order By: Relevance
“…Expression of RCAS1 correlates with invasion or progression in several carcinomas (2,9,10). In addition, RCAS1 expression is associated with poor prognosis in uterine, lung, gallbladder, pancreas, and esophageal carcinoma (11)(12)(13)(14)(15). Although previous studies suggested that RCAS1 is also expressed in colorectal carcinoma cells, the relationship between RCAS1 expression and prognosis in colorectal carcinomas is not known at present.…”
mentioning
confidence: 99%
“…Expression of RCAS1 correlates with invasion or progression in several carcinomas (2,9,10). In addition, RCAS1 expression is associated with poor prognosis in uterine, lung, gallbladder, pancreas, and esophageal carcinoma (11)(12)(13)(14)(15). Although previous studies suggested that RCAS1 is also expressed in colorectal carcinoma cells, the relationship between RCAS1 expression and prognosis in colorectal carcinomas is not known at present.…”
mentioning
confidence: 99%
“…As suspected, it was expressed in all cases of metastatic lymph nodes. RCAS1 was shown to be a ligand for a putative receptor on immune cells such as T cells and natural killer cells [7][8][9][10][11][12][13][14] . Scientists suggest that RCAS1 may play a protective role in tumor cells against immune surveillance by inhibition of clonal expression and inducing receptor-expressing cell death.…”
Section: Resul Resul Resul Resul Results Ts Tsmentioning
confidence: 99%
“…This tumor-associated antigen has been demonstrated in several kinds of gastrointestinal cancer by immunohistochemical study using the specific mouse mAb, 22-1-1. The result of RCAS1 expression was evaluated for the percent incidence in various cancers including gall bladder cancer (70%) [9] , cholangiocarcinoma (85.9-96.4%) [10,11] , gastric cancer (54.3%) [12] , pancreatic cancer (100%) [13] , and colorectal cancer (100%) [14] . However, until now, there has been no intensive study about the expression of RCAS1 in lymph node metastasis from gastrointestinal cancer.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…It also exists in soluble form, probably through alternative splicing (2). Immunohistochemical studies show that RCAS1 is expressed in various malignant tumors, and its expression is one of the important clinicopathological parameters correlating with patient survival (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Soluble RCAS1 has also been detected in blood serum by enzyme-linked immunosorbent assay (ELISA), and is probably released from the membrane as a result of ectodomain shedding (14,15).…”
Section: Introductionmentioning
confidence: 99%